The Impact of Stretching Exercise on Musculoskeletal Pain and Quality of Life of Occupational Therapists - Kurnia, Rina; Sarwi Hastuti, Lis (Poltekkes Kemenkes Surakarta, 2024)
Background: The occupational therapy profession has risks from its work, namely musculoskeletal pain. This problem, if not properly addressed, will have a serious impact, including a deterioration in quality of life. Some attempts that can be made to overcome musculoskeletal pain are pharmacological and non-pharmacological efforts. This study will look at the effect of intervention in the form of stretching exercises on musculoskeletal pain and quality of life in occupational therapists in the Klaten district. The aim of this study is to measure the effect of stretching exercises on musculoskeletal pain and quality of life among occupational therapists in the Klaten district. Methods: This study utilized a pre-experimental pretest-posttest design and employed purposive sampling to select participants. Musculoskeletal pain was assessed using the Nordic Body Map questionnaire, while the WHOQOL-BREF instrument was used to measure quality of life. Results: The study found a statistically significant decrease in musculoskeletal pain with a p-value of 0.000 using a paired t-test. Similarly, both the Wilcoxon signed-rank test and the paired t-test showed statistically significant improvements across all four quality-of-life domains, yielding a p-value of 0.001. Conclusion: Stretching exercise has the effect of reducing musculoskeletal pain and improving the quality of life of occupational therapists in the Klaten district.